PROSEDUR PENERIMAAN DAN PENGELUARAN KAS PADA CV. MAKMUR SEHAT SENTOSA YOGYAKARTA - Anggar Iswari; Hasim As’ari (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
Adequate procedures can support and assist companies to achieve their goals, so that in this service the aim is to find out about cash receipts and disbursement procedures used in CV. Makmur Sehat Sentosa Yogyakarta. For data collection using techniques, namely interviews and documentation. The procedure for receiving and disbursing cash is the object of this service, while the subject of the service is CV. Makmur Sehat Sentosa Yogyakarta. Qualitative data is the data used in this service. For the results of the service, it is explained that the procedure for receiving and disbursing cash at CV. Makmur Sehat Sentosa Yogyakarta includes cash receipts obtained from cash sales and from credit sales, while cash disbursements include regular and non-routine cash disbursements using disbursement procedures with a petty cash fund system. The procedure for receiving and disbursing cash on CV. Makmur Sehat Sentosa Yogyakarta is adequate, this is reflected in the procedures for receiving and disbursing cash in the CV. Makmur Sehat Sentosa Yogyakarta.